2021
DOI: 10.3390/v13102059
|View full text |Cite
|
Sign up to set email alerts
|

Lower Respiratory Tract Infection and Genus Enterovirus in Children Requiring Intensive Care: Clinical Manifestations and Impact of Viral Co-Infections

Abstract: Infection by rhinovirus (RV) and enterovirus (EV) in children ranges from asymptomatic infection to severe lower respiratory tract infection (LRTI). This cohort study evaluates the clinical impact of RV/EV species, alone or in codetection with other viruses, in young children with severe LRTI. Seventy-one patients aged less than 5 years and admitted to the Paediatric Intensive Care Unit (PICU) of a reference children’s hospital with RV or EV (RV/EV) LRTI were prospectively included from 1/2018 to 3/2020. A com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 41 publications
2
9
1
Order By: Relevance
“…The lower respiratory tract infection (LRTI) is mainly induced by virus, mycoplasma, chlamydia and bacteria, etc. In clinic, different pathogens may cause similar symptoms [7][8][9] . It's difficult to identify patient diseases because of the overlap or similar clinical presentations.…”
mentioning
confidence: 99%
“…The lower respiratory tract infection (LRTI) is mainly induced by virus, mycoplasma, chlamydia and bacteria, etc. In clinic, different pathogens may cause similar symptoms [7][8][9] . It's difficult to identify patient diseases because of the overlap or similar clinical presentations.…”
mentioning
confidence: 99%
“…RV infection (RVi) ranges from asymptomatic or mild symptomatic infection to being often the only etiological agent in patients requiring advanced life support in intensive care units. Viral and bacterial coinfections have been considered as factors associated with severe disease, but these results are not consistent between series 1,2 and the wide clinical spectrum of RVi has not been clearly explained by a unique element.…”
Section: Introductionmentioning
confidence: 92%
“…NPA samples were collected from all children according to the standard operating procedure established at the study site. 5 Nasopharyngeal secretions were aspirated using a catheter connected to a vacuum source. The mucus collected within the catheter was then eluted by the aspiration of 1.0 mL sterile phosphate-buffered saline Quality of sequencing data was assessed with the FASTQC toolkit.…”
Section: Laboratory and Bioinformatic Proceduresmentioning
confidence: 99%
“…Nonetheless, most of the published literature does not focus on specific viral coinfections as a factor of severity, and this could be different depending on the viral etiology 4 . In this sense, a recent study from our group that focused on the role of viral coinfection in the specific scenario of RV/EV infection showed that virus codetection appears not to be decisive to cause severe LRTI in young children in a PICU setting 5 …”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation